Phototropin Encoded by a Single-Copy Gene Mediates Chloroplast Photorelocation Movements in the Liverwort Marchantia polymorpha. Issue 1 (5th August 2014) - Komatsu, Aino; Terai, Mika; Ishizaki, Kimitsune; Suetsugu, Noriyuki; Tsuboi, Hidenori; Nishihama, Ryuichi; Yamato, Katsuyuki T.; Wada, Masamitsu; Kohchi, Takayuki
Abstract : Phototropin, encoded by a single-copy gene, mediates chloroplast movements in Marchantia polymorpha, and its expression can rescue the phot mutant defects in vascular plants. Abstract: Blue-light-induced chloroplast photorelocation movement is observed in most land plants. Chloroplasts move toward weak-light-irradiated areas to efficiently absorb light (the accumulation response) and escape from strong-light-irradiated areas to avoid photodamage (the avoidance response). The plant-specific kinase phototropin (phot) is the blue-light receptor for chloroplast movements. Although the molecular mechanisms for chloroplast photorelocation movement have been analyzed, the overall aspects of signal transduction common to land plants are still unknown. Here, we show that the liverwort Marchantia polymorpha exhibits the accumulation and avoidance responses exclusively induced by blue light as well as specific chloroplast positioning in the dark. Moreover, in silico and Southern-blot analyses revealed that the M. polymorpha genome encodes a single PHOT gene, MpPHOT, and its knockout line displayed none of the chloroplast photorelocation movements, indicating that the sole MpPHOT gene mediates all types of movement. Mpphot was localized on the plasma membrane and exhibited blue-light-dependent autophosphorylation both in vitro and in vivo. Heterologous expression of MpPHOT rescued the defects in chloroplast movement of phot mutants in the fern Adiantum capillus-veneris and the seed plant Arabidopsis ( Arabidopsis thaliana ). These results indicate that Mpphot possesses evolutionarily conserved regulatory activities for chloroplast photorelocation movement. M. polymorpha offers a simple and versatile platform for analyzing the fundamental processes of phototropin-mediated chloroplast photorelocation movement common to land plants.